2014
DOI: 10.1186/1471-2407-14-187
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption, cigarette smoking and the risk of subtypes of head-neck cancer: results from the Netherlands Cohort Study

Abstract: BackgroundProspective data on alcohol consumption, cigarette smoking and risk of head-neck cancer (HNC) subtypes, i.e. oral cavity cancer (OCC), oro-/hypopharyngeal cancer (OHPC), and laryngeal cancer (LC), are limited. We investigated these associations within the second largest prospective study on this topic so far, the Netherlands Cohort Study.Methods120,852 participants completed a questionnaire on diet and other cancer risk factors in 1986. After 17.3 years of follow-up, 395 HNC (110 OCC, 83 OHPC, and 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
145
1
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 40 publications
9
145
1
13
Order By: Relevance
“…They reported that alcohol has a synergistic effect with tobacco chewing and smoking (Gangane et al, 2007;Subapriya et al, 2007;Shenoi et al, 2012). Some reports by (Chung et al, 2005;Loyha et al, 2013;Maasland et al, 2014) found in their study that alcohol drinking was significantly associated with oral cancer. In India, there is significant variation across different states regarding both smoking as well as consuming smokeless tobacco.…”
Section: Discussionmentioning
confidence: 95%
“…They reported that alcohol has a synergistic effect with tobacco chewing and smoking (Gangane et al, 2007;Subapriya et al, 2007;Shenoi et al, 2012). Some reports by (Chung et al, 2005;Loyha et al, 2013;Maasland et al, 2014) found in their study that alcohol drinking was significantly associated with oral cancer. In India, there is significant variation across different states regarding both smoking as well as consuming smokeless tobacco.…”
Section: Discussionmentioning
confidence: 95%
“…Adenocarcinoma was detected as a malignant component in all of our patients. The researchers indicated that 25% of 28 patients with CXPA were previously operated due to PA (Nouraei et al, 2005). PA had not developed previously in any of our cases.…”
Section: Discussionmentioning
confidence: 63%
“…Se ha estimado un riesgo relativo de 1,54 para el carcinoma escamoso laríngeo en consumidores de más de 30 grs de alcohol por día y un riesgo relativo de 8,07 para fumadores 17 . En relación a lo anterior, se ha comprobado el rol sinérgico de estos factores al ser combinados 17,18 .…”
Section: Factores De Riesgo Y Prevenciónunclassified